Pengaruh Komunikasi Interpersonal Orangtua dan Kekerasan Fisik terhadap Perilaku Agresif Remaja Gamers - Kurniawan, Vidhya Pudharika (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Interpersonal communication between parents and children is an important matter for children, especially for teenagers, who are undergoing many changes. Unfortunately, physical violence often occurs within this interpersonal communication. Furthermore, the rapid development of technology in society has introduced many online games. Although online games are believed to reduce a person's stres levels, the more time a person spends playing online games, the more their interpersonal relationships decline. This can ultimately lead to aggressive behavior in teenagers themselves. The purpose of this study is to examine the influence of parental interpersonal communication and physical violence on the aggressive behavior of teenage gamers. The method used is quantitative, with data collection techniques in the form of questionnaires distributed to 100 teenage respondents in Jakarta using a random sampling technique. The results of the study show that the parental interpersonal communication variable has a positive and significant influence on adolescent aggressive behavior by 6.825. The physical violence variable has a positive and significant influence on adolescent aggressive behavior by 4.211. Both variables, parental interpersonal communication and physical violence, have a positive and significant influence on adolescent aggressive behavior by 26.028.